Analisis Laporan Keuangan Untuk Menilai Kinerja Pada CV. Aji Yasa Desa Kowang Kecamatan Semanding Tuban - Hariyanti Hariyanti (Fakultas Ekonomi Universitas 45 Surabaya, 2021)
Financial problems are one of the most vital problems for companies in business development in all companies. One of the main goals of establishing a company is to make a profit. However, whether a company is successful in making a profit and maintaining its company depends on financial management. Companies must have healthy and efficient financial performance to gain profits or profits. Therefore, financial performance is important for every company in business competition to maintain its company. A company's ability to generate profits is the key to a company's success in being able to be said to have good company performance, because profit is a component of financial reports which is used as a tool to assess whether the company's performance is good or not. another company. One factor that can show whether a company's performance is good or not is financial report analysis.